A Note on Three “New“ Species of Xylobium (Orchidaceae , Maxillariinae ) from Ruiz and Pavón's Peruvian Collections - Pupulin, Franco (2016)
The recent transfer to the genus Xylobium of three orchid species originally described by Ruiz and Pavón as members of Maxillaria is challenged on the basis of the extant evidence found in the herbarium and the archives of the Royal Botanic Garden, Madrid, where the first set of materials intended for the Flora Peruviana et Chilensis is deposited. The study of the taxonomic literature does not support the claims about a common usage of the three names, Maxillaria alata, M. bicolor, and M. cuneiformis, as being referable to Xylobium.